Gustav Adolf Michaelis (1798-1848) - K. N. Grigorieva (IRBIS LLC, 2020)
Professor Gustav Adolf Michaelis was an outstanding German obstetrician-gynecologist, one of the founders of scientific obstetrics. He gained worldwide recognition for his studies on the "sacral rhombus", named after him the "rhombus of Michaelis". Dr. Michaelis was an honest, hardworking and rather critical person, so in 1847, he did not instantly accept the ideas of Ignaz Philipp Semmelweis's on "preventing puerperal fever". Only in 1848, Michaelis introduced the compulsory chlorine hand washing in his clinic and made sure that mortality had dropped significantly. He was very depressed when he realized how many women (including his beloved niece) died from postpartum fever due to unsanitary obstetric practices. On August 8, 1848, Gustav Adolf Michaelis committed suicide.